2020
DOI: 10.1080/09614524.2020.1836129
|View full text |Cite
|
Sign up to set email alerts
|

The failure of externally-driven advocacy initiatives to contextualise sub-Saharan “marginalised women”

Abstract: This is a repository copy of The failure of externally-driven advocacy initiatives to contextualise sub-Saharan "marginalised women".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[32][33][34] This has ramifications on aid effectiveness; for example, the strong focus on economic growth is often at odds with local perceptions of development. [35][36][37][38] Research has shown that the leadership of development organizations lacks diversity; a recent study found that 32% of CEOs were women, and 3% were BIPOC. 39 Implicitly, because both race and gender did not disaggregate data, these statistics also demonstrate the absent representation of BIPOC women.…”
Section: Literature Review Inequalities In International Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34] This has ramifications on aid effectiveness; for example, the strong focus on economic growth is often at odds with local perceptions of development. [35][36][37][38] Research has shown that the leadership of development organizations lacks diversity; a recent study found that 32% of CEOs were women, and 3% were BIPOC. 39 Implicitly, because both race and gender did not disaggregate data, these statistics also demonstrate the absent representation of BIPOC women.…”
Section: Literature Review Inequalities In International Developmentmentioning
confidence: 99%
“…Many gender scholars have suggested ways of including diverse BIPOC feminisms into development policy and programs; the sanitation sector could lead diversity changes with these recommendations. 36,37,71…”
Section: Influence Of Western Feminismmentioning
confidence: 99%
“…That incorporation required Uganda and its constituent local governments to act in accordance with the government policy framework (Mpiima, Manyire, Kabonesa & Espiling, 2019). Moreover, the previously marginalised groups, mainly the women, the youth and people with disabilities (PWDs), were brought into the mainstream local government programmes (Bedigen, Mdee, Temlong, Thorley & Tshomba, 2020).…”
Section: Introductionmentioning
confidence: 99%